Recommendations and Basic Principles of Phototherapy (Canadian Dermatology Today, 2025)
Phototherapy has long been a cornerstone in dermatology, offered in most dermatology clinics globally. Despite the advent of several new biologic and systemic therapeutics, phototherapy remains a favoured treatment option due to its low side-effect profile and efficacy for treating mild-to-moderate inflammatory dermatoses. It can be used for a variety of skin conditions, including psoriasis, eczema, vitiligo, lichen planus, mycosis fungoides, pityriasis lichenoides, nodular prurigo, pruritus, and morphea.In this article, we will provide an overview of the basic principles of phototherapy, as well as offering recommendations for managing a phototherapy service. Our focus will be on whole-body phototherapy, without the use of psoralens.